Penggunaan Permainan Kartu Bergambar untuk Meningkatkan Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun di TK PGRI 2 Mataram - Suarni, Ni Luh (TSAQOFAH, 2022)
This study aims to find out how much picture card games can improve the early reading skills of children aged 5-6 years in PGRI 2 Mataram Kindergarten in the 2021/2022 academic year. This research is a classroom action research. The subjects in this study were 19 students of TK PGRI 2 Mataram with 8 male students and 11 female students. Based on the results of the research and discussion, it can be concluded that early reading skills in children aged 5-6 years at TK PGRI 2 Mataram can be improved using picture word cards as media. This can be proven from the results of increasing the ability to read early. In the initial conditions the average achievement was 66.67% and an increase of 11.11% so that in Cycle I it reached 77.78% and in Cycle I to Cycle II it increased by 18.71% so that in Cycle II it reached a score of 96 ,49%.